Health-promoting behaviours and concussion history are associated with cognitive function, mood-related symptoms and emotional–behavioural dyscontrol in former NFL players: an NFL-LONG Study. Issue 12 (4th January 2021) - Walton, Samuel R; Kerr, Zachary Y; Brett, Benjamin L; Chandran, Avinash; DeFreese, J D; Smith-Ryan, Abbie E; Stoner, Lee; Echemendia, Ruben J; McCrea, Michael; Meehan, III, William P; Guskiewicz, Kevin M
Abstract : Objectives: To examine the relationships among self-reported sport-related concussion (SRC) history and current health-promoting behaviours (exercise frequency, diet quality and sleep duration) with self-reported measures of brain health (cognitive function, symptoms of depression and anxiety and emotional–behavioural dyscontrol) in former NFL players. Methods: In this cross-sectional study, a questionnaire was sent to former NFL players. Respondents reported SRC history (categorical: 0; 1–2; 3–5; 6–9; 10+ concussions), number of moderate-to-vigorous aerobic and resistance exercise sessions per week, diet quality (Rapid Eating Assessment for Participants—Shortened) and average nightly sleep duration. Outcomes were Patient-Reported Outcomes Measurement Information System Cognitive Function, Depression, and Anxiety, and Neuro-QoL Emotional-Behavioral Dyscontrol domain T-scores. Multivariable linear regression models were fit for each outcome with SRC history, exercise frequency, diet quality and sleep duration as explanatory variables alongside select covariates. Results: Multivariable regression models (n=1784) explained approximately 33%–38% of the variance in each outcome. For all outcomes, SRC history (0.144≤|β|≤0.217) was associated with poorer functioning, while exercise frequency (0.064≤|β|≤0.088) and diet quality (0.057≤|β|≤0.086) were associated with better functioning. Sleeping under 6 hours per night (0.061≤|β|≤0.093) was associated with worse depressive symptoms, anxiety and emotional–behavioural dyscontrol. Conclusion: Several variables appear to be associated with mood and perceived cognitive function in former NFL players. SRC history is non-modifiable in former athletes; however, the effects of increasing postplaying career exercise frequency, making dietary improvements, and obtaining adequate sleep represent important potential opportunities for preventative and therapeutic interventions.